Peleg and Weibull models for water absorption of copolymer gels crosslinked on polyethylene glycol dimethacrylates - Ismail, Osman (SPRINGER, 2014)
In this study, the super-absorbent copolymer gels were obtained from the aqueous solution of monomers dispersed in a continuous organic phase. The inverse suspension polymerization was accomplished with the use of aqueous solutions of partly neutralized acrylic acid with a predetermined crosslinker agent, polyethylene glycol dimethacrylates (PEGDMA)/monomer ratio in cyclohexan. The copolymer gels synthesized using PEGDMA crosslinker with three different molecular weights (PEGDMA(330), PEGDMA(550), and PEGDMA(750)) were characterized by A +/- nfrared spectroscopy and scanning electron microscopy. Water absorption capacities of the copolymer gels were determined. The water absorption capacity of 1 g copolymer gels in water was respectively obtained as 232, 255, and 316 g water/g polymer gel for PEGDMA(330), PEGDMA(550), and PEGDMA(750), respectively. The Peleg and Weibull models were used to describe the water absorption behavior of the copolymer gels. The highest values of R (2) and the lowest values of chi (2) and RMSE for copolymer gels were observed with the Weibull model.
Keywords: Absorption; Copolymer gel; Modeling; Peleg; Weibull; POLYELECTROLYTE GELS; HYDRATION KINETICS; INVERSE SUSPENSION; SUPERABSORBENT; HYDROGELS; POLYMERS; ACRYLATE; BEHAVIOR; Chemistry